IMPLIKASI KERJA SAMA INDONESIA JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) DALAM MENINGKATKAN EKSPOR KOMODITAS IKAN TUNA PADA TAHUN 2014-2019 - Tegar Bramantya, (2023)
This research focuses on the cooperation carried out by Indonesia and Japan in the tuna trade sector, whether it is the various efforts or policies adopted by Indonesia to increase exports of its tuna commodity, whether in negotiating to reduce the import duty tariff for Indonesian tuna to Japan, or through various promotions of Indonesian domestic trade and investment conducted by Japan. Economic cooperation carried out by Indonesia and Japan can be analyzed using the theory of bilateral cooperation and international trade which is the basis used to analyze research problems. Indonesia's economic cooperation with Japan in an effort to increase Indonesia's tuna exports to Japan for the 2014-2019 period is a bilateral relationship that is established to fulfill national interests, especially from the trade sector through the performance of tuna exports and the cooperation undertaken to increase exports of tuna commodities, tariffs The entry of tuna is considered to be an obstacle to trade relations between the two. Protectionism in the form of import duty rates is a form of prevention and protection for local producers, but this policy is also contrary to the principles of the Economy Partnership Agreement (EPA) incorporated in the IJEPA framework. This certainly makes the Indonesian Government make every effort or diplomacy with the Japanese Government to be able to reduce the import duty rates for Indonesian tuna to Japan. The research method used is descriptive qualitative research using primary data sourced from official data from the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia and the results of interviews with agencies and figures related to the research conducted by the author. While secondary data was obtained from books, journals, archives, documentation, news, press releases, and articles which can be used as references in supporting research arguments